Effects of Vitamin D Supplementation on Blood Glucose Levels in Streptozotocin-Induced Diabetic Rats - Hansah, Rendri Bayu; Dhuha, Alief; Susanti, Melya; Sari, Widia; Khudri, Ghaniyyatul; Handayani, Kurnia Maidarmi (Health and Medical Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion, insulin resistance, or both. Poor glycemic control in DM leads to complications such as cardiovascular disease and nephropathy. Vitamin D has been suggested to influence glucose metabolism by improving insulin secretion and sensitivity thorugh mechanisms involving pancreatic β-cells and anti-inflammatory pathways. This study evaluates the effect of vitamin D supplementation on blood glucose levels in diabetic rats. An experimental study was conducted using 25 males Sprague Dawley rats, divided into five groups: Group A (negative control), Group B (non-DM + 415 IU/kgBW vitamin D), Group C (DM without vitamin D), Group D (DM + 415 IU/kgBW vitamin D), and Group E (DM + 1100 IU/kgBW vitamin D). Diabetes was induced using streptozotocin (50 mg/kg BW), and rats with random blood glucose levels >200 mg/dL were considered diabetic. Vitamin D supplementation was given via gavage for 30 days. Serum vitamin D and random blood glucose levels were measured 30 days after supplementation. Statistical analyses included ANOVA and Pearson correlation tests. Vitamin D supplementation significantly increased serum vitamin D levels in diabetic rats, especially in Group E (DM + 1100 IU/kgBW vitamin D; (p < 0.05). Random blood glucose levels decreased significantly in diabetic groups and Group E showed the largest glucose reduction (p < 0.001). A moderate negative correlation (r = -0.47, p = 0.017) between vitamin D levels and glucose changes was observed. Vitamin D supplementation reduces blood glucose levels in diabetic rats, with higher doses showing greater efficacy. These findings highlight vitamin D’s potential as an adjunctive therapy for diabetes management. Further research is needed to explore underlying mechanisms.